Police Position-oriented Preventive Strategies in the Fight Against Terrorist Crimes - Ebrahim Rajabi Tajamir (Faṣlnāmah-i Pizhūhish-i Huqūq-i Kiyfarī, 2021)
The global problem of terrorism, which has called on all governments to fight, requires serious measures to prevent security damage in addition to effectively confronting its policymakers. Therefore, resisting terrorism without strategic planning will intensify security measures. Method: The present research has been applied in terms of collecting information by documentary method and by studying international documents, sources related to the subject and the obtained information has been analyzed descriptively-analytically. Results: The most important components of the target of terrorist attacks; exposure, vitality, symbolism, legitimacy, destructibility, crowdedness, proximity, and ease of access are all chosen by terrorists in a rational process. Conclusion: In fact, each target is assessed in terms of the risk of terrorist attacks and, consequently, with police-oriented strategies such as reducing the target of crime, electronic surveillance, the physical presence of police in hot areas, controlling surveillance, identifying hot spots and potential criminals, designing an anti-terrorism environment and increasing police awareness can all prevent terrorist attacks.